Lynch syndrome caused by MLH1 mutations is associated with an increased risk of breast cancer: a cohort study. Issue 8 (22nd June 2015) - Harkness, Elaine F; Barrow, Emma; Newton, Katy; Green, Kate; Clancy, Tara; Lalloo, Fiona; Hill, James; Evans, D Gareth
Abstract : Introduction: Lynch syndrome is known to cause an increased risk of malignancies, including bowel and endometrial cancers. However, the risk of breast cancer associated with mutations in the mismatch repair (MMR) genes that cause Lynch syndrome is still unclear. Materials and methods: This study assesses the cumulative risk of breast cancer in 106 MLH1 and 118 MSH2 families. Families were referred on the basis of clinical criteria. Pedigree information was obtained, and tumour immunohistochemistry and microsatellite testing performed. Appropriate patients underwent sequencing and multiple ligation dependent probe amplification of all relevant exons of the MMR genes. Kaplan–Meier analysis of cumulative lifetime risk of breast cancer was made combining proven mutation carriers and their first-degree female relatives. Results: After allocation of mutation status, the cumulative risk of breast cancer to 70 years in MLH1 carriers was 18.6% (95% CI 11.3 to 25.9)). This is significantly higher than the cumulative risk for MSH2 which was 11.2% (95% CI 1.4 to 21.0) to age 70 years (p=0.014). The UK population risk is 7.5%–8% at the age of 70 years. Prospective analysis identified six breast cancers in 1120 years of follow-up with an OR of 3.41 (95% CI 1.53 to 7.59). Discussions: Female MLH1 carriers would appear to be at moderate risk of breast cancer and should be considered for breast screening at ages earlier than national screening programmes.